A symbiosis theory-based strategic framework for rural landscape assessment: a case study utilizing AHP and system dynamics - Xiao, Xiaomei; Zhuang, Ji’an; Wang, Mo; Wang, Lie (Frontiers in Environmental Science, 2025)
Rural landscape quality assessments are crucial for sustainable development, particularly in the context of China’s rural revitalization strategy. This study delineates the integration of the Analytic Hierarchy Process (AHP) and System Dynamics (SD) within a symbiotic framework to assess rural landscape quality, using Pingpan Village as a case study. The research highlights the importance of focusing on symbiotic environmental factors and demonstrates how such a focus enhances the integration of ecological, cultural, and functional elements essential for the sustainability and resilience of rural communities. By employing AHP, the study systematically quantifies and weights diverse landscape features, while SD captures the temporal and psychological dimensions of visitor experiences. The results reveal that ecological quality is the highest-scoring indicator, with a composite score of 0.6190, categorizing the landscape quality as satisfactory. However, areas such as landscape dynamism and functional diversity require significant improvement. This study provides an important framework for policymakers and planners aiming to enhance rural sustainability, emphasizing the integration of diverse landscape components. Future research should explore its application across various rural settings and incorporate advanced technologies like GIS for improved assessment precision.